PERAN GURU ASWAJA DALAM MENANAMKAN NILAI-NILAI PENDIDIKAN KEASWAJAAN SEBAGAI UPAYA STRATEGI DERADIKALISASI DI MTSN 17 JOMBANG - Alifia Zuhriatul Alifa; Qurroti A’yun; Zuhkhriyan Zakaria (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Teachers have a very important role in instilling character values in students in schools, especially religious education based on ahlussunnah wal jama'ah. This pandemic period has had a significant effect in the field of education, one of which is the use of high technology. Therefore, students are required to follow it by studying and looking for supporting materials on the internet. This results in students having the potential to experience errors in understanding the material they are looking for because they come from sources that cannot be accounted for and in the end the potential for students to be radical is greater. The researcher formulates problems about the concepts, roles, and factors that influence the aswaja teacher in instilling the values of private education at MTsN 17 Jombang. This study aims to describe the concepts, roles, and factors that influence the aswaja teacher in instilling the values of private education at MTsN 17 Jombang. The study used a descriptive qualitative approach. Researchers used data collection techniques, namely observations, interviews, and documentation that the researchers had done, the aswaja teacher carried out the inculcation of self-awareness values well.